Nanoscale magnetometry with a microcontroller-based magnetometer using a single nitrogen-vacancy defect in nanodiamond - SÁNCHEZ, Edwin Danelli Coronel (2020)
In the last few years, the study of the negatively charged nitrogen-vacancy (NV−) defect in diamond has increased in many areas of science because of its interesting optical and spin properties, such as high photostability and possibility of performing coherent control of their spin states even under ambient conditions. This makes the NV− defect attractive for the development of diverse application areas such as nanomagnetometry, quantum information processing and nanobiothermometry, as well as for the development of new applications in the spintronic area and quantum technology. The NV− defect is a solid-state system that presents extraordinary sensitivity to magnetic fields and allows sensing schemes with high spatial resolution. Moreover, its paramagnetic triplet ground state evidences predominantly spin-spin interaction that splits the spin projection mgs = 0 from the degenerate state mgs = ±1 by Dgs = 2.87 GHz. With the action of an external local magnetic field the degeneracy is lifted by Zeeman effect and the energy levels splitting is proportional to the projection of magnetic field along to the defect symmetry axis, to which the magnetic dipole moment of the NV− center is parallel. This particular characteristics, together with its nanometric scale, allows building nanomagnetometers that work simply by probing the electronic ground state by Optically Detected Magnetic Resonance (ODMR). In the present work, an ODMR−based system for performing nanomagnetometry was developed using an Arduino Due board microcontroller as a main tool for the magnetometer implementation by means of an established in-system programming. The implemented nanomagnetometry method is simple and relies on the frequency modulation of the NV−defect electron spin resonance (ESR). This is done by introducing in the system an alternated magnetic field produced by also alternated current square pulses that passes through a wire loop located in the vicinity of the nanodiamond. An important fact is that the method uses a single microwaves source to excite spin transitions. The alternating magnetic field produced by the switching of an electric current modulates the NV− ESR central frequency at a conveniently chosen frequency. Since an in-system programming is established, it is possible compute a differential photon counting technique in phase with the modulated field obtaining a signed error signal. The microcontroller is responsible both for controlling the modulated field through the current pulse and for calculating the error signal. The resulting imbalance in photon counts is then used to detect the Zeeman shift in the ESR central frequency applying an ODMR approach. The developed system has a reasonable sensitivity of 4 µT/√Hz and is able to measure magnetic field variations at a rate of around 4 mT/s. This system was used for nanoimaging the inhomogeneous spatial magnetic field profile of a magnetized steel microwire, and a spatial magnetic field gradient of 13 µT/63 nm was measured. Besides, its usefulness in nanoscale imaging of magnetic fields, the present work can be of interest in development of compact nanodiamond based magnetometer.